Including Transgender Students in School Physical Education. Issue 3 (23rd March 2016) - Foley, John T.; Pineiro, Court; Miller, Dan; Foley, Melissa L.
Abstract : The purpose of this article is to provide information for successfully working with students who identify as transgender. It provides insight into the topic from the perspective of an elementary school physical educator and that of a student.